Effect of etching as pre-treatment for electroless copper plating on silicon wafer - Mior Shahidina, Shazatul Akmaliah; Fadila, Nor Akmal; Yusopa, Mohd Zamri; Tamina, Mohd Nasir; Osman, Saliza Azlina (Penerbit UTM Press, 2017)
Metallic coatings, such as copper films can be easily deposited on semiconductor materials like silicon wafer without prior surface pre-treatment using the electroless process. However, the adhesion of the copper film can be very weak and can easily peels off. In this study, the effect of etching in hydrofluoric acid solution as a surface pre-treatment prior to electroless plating on silicon wafer was studied. The etching time in hydrofluoric acid was varied at 1, 3 and 5 minutes in order to investigate the adhesion behaviour of the coating layer. The surface morphology of the electroless plated samples was observed using a field emission scanning electron microscope (FESEM) and the coating thickness was measured using cross sectional analysis. The results showed that longer etching time (5 minutes) produced thicker Cu deposits (8.5μm) than 1 minute etching time (5μm). In addition, by increasing the etching time, the mechanical bonding between the copper film and the substrate is improved.